2014
DOI: 10.3109/0284186x.2014.892209
|View full text |Cite
|
Sign up to set email alerts
|

Radiation-induced trismus in the ARTSCAN head and neck trial

Abstract: Trismus, a well-known sequelae after treatment of head and neck cancer, decreases a patient's oral function and quality of life. The main objectives of this study were to: 1) investigate the long-term prevalence of radiation-induced trismus in patients treated for head and neck cancer according to two different fractionation schedules; and 2) model a dose-response relationship for trismus. Material and methods. Patients were recruited from the Swedish ARTSCAN trial, a prospective randomised multicentre study c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
90
5

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(101 citation statements)
references
References 24 publications
6
90
5
Order By: Relevance
“…In this study, the adjunctive treatments, such as chemotherapy and surgery, had no influence on the mouth opening of the volunteers, just as with the study by Lindblom et al 13 which showed no connection between surgery and mouth opening limitations. With regard to chemotherapy, Bragante et al 9 noted no variation in mouth opening measurements.…”
Section: Discussionsupporting
confidence: 62%
“…In this study, the adjunctive treatments, such as chemotherapy and surgery, had no influence on the mouth opening of the volunteers, just as with the study by Lindblom et al 13 which showed no connection between surgery and mouth opening limitations. With regard to chemotherapy, Bragante et al 9 noted no variation in mouth opening measurements.…”
Section: Discussionsupporting
confidence: 62%
“…Possible confounding factors, such as dose from brachytherapy, were accounted for in our analyses and predicted trismus rates by our models were in corresponded well with the observed rates. In line with others, we based our analyses on mean absorbed structure doses as this dose metric have been reported suitable to describe relationships between various mastication structures and trismus [7][8][9][10][11]. Acknowledging that DVH points typically are strongly correlated, it is not likely that investigating other dose or volume metrics for our purpose of identifying critical structures for radiation-induced trismus would have altered the presented results substantially.…”
Section: Discussionmentioning
confidence: 71%
“…Other studies have also suggested that dose to the masseter is associated with a higher risk of trismus [8,9,11]. In particular, both Lindblom et al [8] and, and more recently, Rao et al [9] found dose to the ipsilateral masseter muscle to provide superior statistics in predicting trismus (defined by Risk structures receiving substantial dose from brachytherapy (more than a maximum absorbed doses of 3.0 Gy or more than mean absorbed doses of 2.0 Gy) were excluded from analysis of that specific structure. MIO 35 mm and CTCAE grade !1, respectively) than dose to other investigated structures (pterygoids (both), TMJ (13), and temporalis (9)).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Biological evaluation was done for several clinical endpoints based on modern NTCP models with both, underlying patient characteristics and treatment procedures similar to the presented study: Incidence of acute oral mucositis (grade Ն 3) [9], aspiration assessed by videofl uoroscopy [10], xerostomia 12 months after therapy [11], subjective and objective swallowing dysfunction [12], late larynx edema (grade Ն 2) [13] and trismus assessed as jaw-opening Ͻ 35 mm [14], cf. Jakobi et al [5] for details.…”
Section: Evaluation Of Treatment Plansmentioning
confidence: 99%